Dose Body Mass Index (BMI) Fit to Muscular Individual? - Habibzadeh, Nasim (International Physiology Journal, 2018)
Body mass index (BMI) seemingly is an important scale for the body types determination in individual with different ethnicity. Accordingly, individual with BMI< 18.5 are classified as slim or underweight and people with BMI between 18.5 -24.9 are called normal body types. Subsequently, those individual with BMI between 25-29.9 are categorized as overweight and people with BMI > 30 are classified as obese people. Nonetheless, important question is where the muscular individual are located in this BMI scale ? Macular induvial also called overweight or obese in BMI scale which can create kind of confusion for induvial because the might try to lose weight whilst they do not actually need it. Thus ,it seems BMI measure is not sensible measure for muscular induvial as otherwise the can be at risk of health problems in various ways. Uses of the another apparatus such an ordinary weight scale or computational devices which could estimate the body type according to the BMI more accurately can be helpful.
Keywords: BMI; Obese; Slim; Muscular; Body type